2012
DOI: 10.1039/c2cc17727g
|View full text |Cite
|
Sign up to set email alerts
|

On the abundance of chiral crystals

Abstract: A common perception of many chemists is that non-biological chiral crystals comprise a small fraction of all crystals, as is the case of chiral non-biological molecules (~10%). We show that the proportion of non-biological chiral crystals is as high as 23%; and only ~6% of these are labelled as chiral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
82
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 32 publications
(15 reference statements)
0
82
0
3
Order By: Relevance
“…8,9 However, in the past two decades, the research on the chiral transfer between organics and inorganics has gained increasing attention, and a series of synthetic inorganics have been endowed with chirality by molecular imprinting from small chiral organic molecules (on the molecular scale) or by copying the helical shapes (with helical pitch sizes over tens of nanometers) of organic templates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 However, in the past two decades, the research on the chiral transfer between organics and inorganics has gained increasing attention, and a series of synthetic inorganics have been endowed with chirality by molecular imprinting from small chiral organic molecules (on the molecular scale) or by copying the helical shapes (with helical pitch sizes over tens of nanometers) of organic templates.…”
mentioning
confidence: 99%
“…8,9 However, in the past two decades, the research on the chiral transfer between organics and inorganics has gained increasing attention, and a series of synthetic inorganics have been endowed with chirality by molecular imprinting from small chiral organic molecules (on the molecular scale) or by copying the helical shapes (with helical pitch sizes over tens of nanometers) of organic templates. 10,11 Interestingly, without the combination of external chiral components, it has been demonstrated that some natural and synthetic chiral inorganics could be directly applied to the enantioselective separation and synthesis of chiral organic small molecules (e.g., amino acids, glucoses).…”
mentioning
confidence: 99%
“…In fact, the Cambridge Structural Database (CSD) includes about seven hundred thousand of crystal data, and remarkably over 70% of organic crystals involve the 21 operations [41]. Moreover, about 10% belong to chiral crystals composed of achiral molecules [36][37][38][39]. These facts indicate that it still remains open to interpret a mechanism for generating supramolecular chirality through the 21 operation.…”
Section: Conventional Idea For Chirality Generation In Major Crystalsmentioning
confidence: 99%
“…Sixty-five among 230 groups are known as the chiral Sohncke symmetry space groups [39]. When symmetry operations are discriminable in chirality by themselves, they hold a pair of notations.…”
Section: Chiral Space Groupsmentioning
confidence: 99%
See 1 more Smart Citation